Prostate-associated gene 4 (PAGE4), an intrinsically disordered cancer/testis antigen, is a novel therapeutic target for prostate cancer - Kulkarni, Prakash (Asian J Androl, 2016)
Prostate-associated gene 4 (PAGE4) is a remarkably prostate-specific Cancer/Testis Antigen that is highly upregulated in the human fetal prostate and its diseased states but not in the adult normal gland. PAGE4 is an intrinsically disordered protein (IDP) that functions as a stress-response protein to suppress reactive oxygen species as well as prevent DNA damage. In addition, PAGE4 is also a transcriptional regulator that potentiates transactivation by the oncogene c-Jun. c-Jun forms the AP-1 complex by heterodimerizing with members of the Fos family and plays an important role in the development and pathology of the prostate gland, underscoring the importance of the PAGE4/c-Jun interaction. HIPK1, also a component of the stress-response pathway, phosphorylates PAGE4 at T51 which is critical for its transcriptional activity. Phosphorylation induces conformational and dynamic switching in the PAGE4 ensemble leading to a new cellular function. Finally, bioinformatics evidence suggests that the PAGE4 mRNA could be alternatively spliced resulting in four potential isoforms of the polypeptide alluding to the possibility of a range of conformational ensembles with latent functions. Considered together, the data suggest that PAGE4 may represent the first molecular link between stress and prostate cancer (PCa). Thus, pharmacologically targeting PAGE4 may be a novel opportunity for treating and managing patients with PCa, especially patients with low-risk disease.